Ion Transport through C-butyl-pyrogallol[4]arene-loaded Poly(Vinyl Chloride) Membranes - de Lima Koller, Silvânia Marilene; Correia, Henrique Dias; Teodósio, Tiago Mateus Bezerra; Cavallini, Thiago de Souza; Demets, Grégoire Jean-François (Journal of Research Updates in Polymer Science, 2021)
The present paper studies the natural diffusion and migration of monovalent aqueous ions through pyrogallol[4]arene cavitand-loaded poly(vinyl chloride) solid-state membranes exposed to concentration gradients, and electric fields using electrodes coated with such membranes. We have observed that ion flux through these semipermeable membranes is directly proportional to the amount of macrocycle they contain. Ion size, in this particular case, is not the most important factor to limit ion flux, but solvation numbers and energies seem to play a much more important role in the whole process.